PENGARUH NILAI-NILAI TUNJUK AJAR UNTUK MENINGKATKAN HUBUNGAN SOSIAL SISWA TERISOLIR MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 5 PEKANBARU - Dirmayanto, Eko; Saam, Zulfan; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to examine the effect of teaching point values to improve social relations of isolated students through group guidance in public high school 5 Pekanbaru. Instructional teaching is all kinds of advice, guidance, advice, trust, teaching, and exemplary examples that benefit human life in a broad sense that contain the noble values of Islamic religion and are in accordance with the culture and social norms adopted by the community. This type of research is quantitative in experimental mode using the design of One-Group Pretest-Posttest Design. The measuring instrument used in this study is sociometry and the scale of social relations. Sociometry used is sociometry with multilevel scale. Determination of the sample using purposive sumpling technique, by processing the results of sociogram and getting 7 isolated students from class X IPS in Pekanbaru Public High School 5, from 7 isolated students were given the scale of social relations and identified as having low social relations. The data analysis technique used was a non-parametric statistical technique using the Wilcoxon test. The results showed that there were differences in the social relations of isolated students before and after given the Teachers' Point values with a significance value of 0.018 <0.05. This means that there are differences between the level of social relations of students isolated before and after given the values of Teachers. Furthermore, based on the Spearman rank test it is known that there are influences of Teachers' Point values on social relations of isolated students with a significance value of 0.021 <0.05. The Effect of Teaching Point Values on social relations of isolated students is 69% while 31% is influenced by other factors that originate from within and from the student's environment. It can be concluded that the teaching values are influential to improve social relations of isolated students through group guidance.Key Words: Teaching point values, Social Relations